Difficulty in Advancing Flexible Epidural Catheters When Establishing Labor Analgesia: An Observational Open-Label Randomized Trial. (July 2021) - Pancaro, Carlo; Purtell, Jasmine; LaBuda, Dana; Saager, Leif; Klumpner, Thomas T.; Dubovoy, Timur; Rajala, Baskar; Singh, Shubhangi; Cassidy, Ruth; Vahabzadeh, Christie; Maxwell, Sean; Manica, Virgil; et al.
Abstract : BACKGROUND: While flexible epidural catheters reduce the risk of paresthesia and intravascular cannulation, they may be more challenging to advance beyond the tip of a Tuohy needle. This may increase placement time, number of attempts, and possibly complications when establishing labor analgesia. This study investigated the ability to advance flexible epidural catheters through different epidural needles from 2 commonly used, commercially available, epidural kits. METHODS: We hypothesized that the multiorifice wire-reinforced polyamide nylon blend epidural catheters will have a higher rate of successful first attempt insertion than the single-end hole wire-reinforced polyurethane catheters for the establishment of labor analgesia. The primary outcome was a difference in proportions of failure to advance the epidural catheter between the 2 epidural kits and was tested by a χ 2 test. Two-hundred forty epidural kits were collected (n = 120/group) for 240 laboring patients requesting epidural analgesia in this open-label clinical trial from November 2018 to September 2019. Two-week time intervals were randomized for the exclusive use of 1 of the 2 kits in this study, where all patients received labor analgesia through either the flexible epidural catheter "A" or the flexible epidural catheter "B." Engineering properties of the equipment used were then determined. RESULTS: Flexible epidural catheter "A, " the single-end hole wire-reinforced polyurethane catheter, did not advance at the first attempt in 15% (n = 18 of 120) of the parturients compared to 0.8% (n = 1 of 120) of the catheter "B, " the multiorifice wire-reinforced polyamide nylon blend epidural catheter ( P < .0001). Twenty-five additional epidural needle manipulations were recorded in the laboring patients who received catheter "A, " while 1 epidural needle manipulation was recorded in the parturients who received catheter "B" ( P < .0001). Bending stiffness of the epidural catheters used from kit "B" was twice the bending stiffness of the catheters used from kit "A" (bending stiffness catheters "A" 0.64 ± 0.04 N·mm 2 versus bending stiffness catheters "B" 1.28 ± 0.20 N·mm 2, P = .0038), and the angle formed by the needle and the epidural catheter from kit "A" was less acute than the angle formed from kit "B" (kit "A" 14.17 ± 1.72° versus kit "B" 21.83 ± 1.33°, P = .0036), with a mean difference of 7.66° between the 2 kits' angles. CONCLUSIONS: The incidence of an inability to advance single-end hole wire-reinforced polyurethane catheter was higher compared to the use of multiorifice wire-reinforced polyamide nylon blend epidural catheter. Variation of morphological features of epidural needles and catheters may play a critical role in determining the successful establishment of labor epidural analgesia.